Reproduction of Islamic Law in The Era of Globalization and Pluralism - Nasaruddin Umar; Irvan Mawardi; Akiho Tsuji; Tuti Haryanti (Jurnal Hukum dan Peradilan, 2023)
The rise of globalization values: secularism, capitalism, legal liberalization and democratic freedom that is sweeping the world today can create a disharmony of diversity during legal pluralism that exists in Indonesia between state law, religious law and customary law. The context of reproduction in this study redesigns policies based on Islamic law that have a vision that can moderate diversity in Indonesia so that the existence of Islamic law can be accepted in the context of diversity and diversity in an inclusive manner. To conduct the research, the author uses conceptual approaches and statutory law. As a result, the author concluded that legal pluralism in Indonesia should not occur strong autonomy in each legal system but increasingly interact and interconnect in the context of moderation, this complementary reproduction model of pluralism is being designed in this study.